Study of maternal outcome in emergency peripartum hysterectomy at a tertiary hospital - K., Varalakshmi; Rastogi, Radha; Choudhary, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Emergency peripartum hysterectomy is an indispensable part of the obstetricians’ armamentarium. In no other gynecological or obstetrical surgery, is the surgeon in as much a dilemma as when deciding to resort to an emergency hysterectomy. On one hand, it is the last resort to save a woman’s life and on the other hand, her reproductive capability is sacrificed. Many times, it is a very difficult decision and requires good clinical judgment. Objective of present study was to study the cases of emergency peripartum hysterectomy performed in tertiary care center to estimate the incidence, indications, and maternal outcome following the procedure. Methods: All cases of peripartum emergency hysterectomy that were performed in our hospital from January 2015 to June 2016 were reviewed and evaluated in terms of the incidence, indications, and the associated complications. Results: During the study period there were 28 emergency peripartum hysterectomies out of 28215 deliveries giving an incidence of 0.10%. rupture uterus was the Commonest indication contributing to 13 cases. Septicemia was the common post operative complication associated. There were 4 maternal deaths in our study. Conclusions: Emergency peripartum hysterectomy though a rare operation, still remains a life‑saving procedure with which every obstetrician must be conversant. regular antenatal care, identification of high‑risk cases, and prompt referral can reduce the incidence of this operation. Peripartum hysterectomy will always remain an essential life saving surgery for the mother at cost of their uterus and when performed in indicated cases at right time will help in bringing down maternal mortality.